2018
DOI: 10.1515/chem-2018-0006
|View full text |Cite
|
Sign up to set email alerts
|

The preparation and antibacterial activity of cellulose/ZnO composite: a review

Abstract: The infectious diseases caused by various bacteria pose serious threat to human health. To solve this problem, antibacterial agents have been widely used in people’s daily life to deactivate or kill these bacteria. Among the antibacterial agents, ZnO is one of the most promising metal oxide antibacterial agents due to its non-toxic nature and safe properties. To expand its application, many composites of ZnO have been widely studied. Cellulose, as one of the most abundant biopolymers, has many merits like biod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(39 citation statements)
references
References 89 publications
2
37
0
Order By: Relevance
“…The release values are less than zinc levels in human blood plasma, which is 0.78-1 mg/L (Bettger & O'Dell, 1993), which suggests that the ZnO remaining in the fiber, not only the release of Zn, may also be contributing to cell differentiation. Studies which incorporate zinc and ZnO into bioactive coatings show improvement in cellular response and antibacterial activity (K. Li et al, 2013;Memarzadeh, Sharili, Huang, Rawlinson, & Allaker, 2015;Ramaswamy, Wu, Zhou, & Zreiqat, 2008;Zhao, Guo, Hu, Guo, & Pan, 2018). Live/dead studies showed no differences between ZnO composite scaffolds and PCL control.…”
Section: Discussionmentioning
confidence: 99%
“…The release values are less than zinc levels in human blood plasma, which is 0.78-1 mg/L (Bettger & O'Dell, 1993), which suggests that the ZnO remaining in the fiber, not only the release of Zn, may also be contributing to cell differentiation. Studies which incorporate zinc and ZnO into bioactive coatings show improvement in cellular response and antibacterial activity (K. Li et al, 2013;Memarzadeh, Sharili, Huang, Rawlinson, & Allaker, 2015;Ramaswamy, Wu, Zhou, & Zreiqat, 2008;Zhao, Guo, Hu, Guo, & Pan, 2018). Live/dead studies showed no differences between ZnO composite scaffolds and PCL control.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the recombination of the photo-generated holes in the valence band with the photo-excited electrons in the conduction band, which results in the dissipation of heat, which impairs ZnO's photocatalytic effectiveness. ZnO Ps can be produced by two main approaches, namely, the top-down approach, which is also called the metallurgical process and is based on the roasting of the rare mineral zincite, and the bottom-up approach, which includes various physical and chemical synthesis techniques, among which mechanochemical, electrochemical, sonochemical, hydrothermal, solvothermal, ultrasonic, microwave irradiation, sol-gel, microemulsion, coagulation, controlled precipitation methods, and others, have already been introduced [2,4,28,39,43]. To avoid the use of non-eco-friendly, toxic, and unsafe reagents, the green synthesis of ZnO Ps has become an important alternative to conventional physio-chemical processes.…”
Section: Characteristics Of Znomentioning
confidence: 99%
“…Review articles dealing with the use of ZnO in textiles are rare [2,[37][38][39][40]. They are primarily focused on novel application procedures of ZnO [2], being limited to the preparation of antibacterial cellulose/ZnO composites [39] or antimicrobial fabrics containing metal-based nanoparticles, among them ZnO NPs [40]. Existing articles discuss the applications of nanomaterials to textile substrates to obtain different functional properties [38] or give an overview of the development of photocatalystmodified textiles more generally [37].…”
Section: Introductionmentioning
confidence: 99%
“…Adding inorganic nanoparticles (like Ag, ZnO, TiO 2 , Fe 3 O 4 , etc.) and essential oils in such polymeric films will improve both WVP and antimicrobial activity [ 111 , 148 , 149 , 150 , 151 ].…”
Section: Biodegradable Polymeric Antimicrobial Packagingmentioning
confidence: 99%